REVIEW PAPER Necrotizing fasciitis – life-threatening disease - Stec-Tatarynowicz, Marta; Kanikowska, Alina; Pawlaczyk, Mariola; Pawlaczyk, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Necrotising fasciitis is a rare, life-threatening infection of fascia, subcutaneous fat and skin. Necrosis of the tissue is related to ischaemia due to thrombosis of the subcutaneous vessels. It affects more frequently people with immunodeficiency. There are different types of cellulitis and it is essential to recognize necrotizing fasciitis early for applying surgical intervention along with antibiotic therapy. Prompt diagnosis and treatment may prevent from death which is a considerable outcome of this condition. The aim of this article is to review current knowledge on the pathology, clinical course and treatment of the disease.